2022
DOI: 10.1007/s00384-022-04191-x
|View full text |Cite
|
Sign up to set email alerts
|

Disparate age and sex distribution of sessile serrated lesions and conventional adenomas in an outpatient colonoscopy population–implications for colorectal cancer screening?

Abstract: Purpose Colorectal cancer (CRC) is increasingly diagnosed in individuals aged < 50 years, resulting in advocacy of screening from age 45 years. Despite existing knowledge associating CRC with conventional adenomas, the significance of sessile serrated lesions (SSLs) on the burden of CRC is less detailed. We aimed to provide contemporary estimates for SSL prevalence and examine patient and procedure factors associated with SSL detection. Methods Retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 54 publications
(75 reference statements)
4
11
0
Order By: Relevance
“…A number of studies have shown the majority of SP to be located in the right colon. 14,16 this observation has been implicated in the development right sided colon cancer. 16 We found the majority of CSSL to be located in the distal colon (56.3%).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…A number of studies have shown the majority of SP to be located in the right colon. 14,16 this observation has been implicated in the development right sided colon cancer. 16 We found the majority of CSSL to be located in the distal colon (56.3%).…”
Section: Discussionmentioning
confidence: 84%
“…The results from this study show that patients aged 40–49 had lower adenoma detection rate (ADR) and serrated polyp detection rate (SPDR, 13.1% and 3.6%) compared to other age groups. However, other Australian studies have reported higher rates of adenomatous (AP) and serrated polyps (SP) in younger patients and especially in females 12,14 . Patients aged 40–49 years old who underwent colonoscopy for positive faecal occult blood had a higher ADR and SPDR of 25.0% and 6.3% respectively when compared to other indications for colonoscopy in this age group (Table S2).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…An Australian cohort study found that SP in younger patients may have a lower potential for malignancy than in older patients [16]. In contrast, another Australian cohort study hypothesized that SSL in younger women may be part of the reason for the rising incidence of CRC in women aged < 50 years [30]. However, whether there is a difference in SSL incidence in males and females remains unclear.…”
Section: Discussionmentioning
confidence: 99%